The improvement of tribological parameters of nano structural multilayer coatings for unipolar modular joint applications - Zykova, Anna; Safonov, Vladimir; Lukyanchenko, Volodimir; Samoilenko, Olexsandr; Korzh, Mykola; Yakovin, Stanislav; Kolesnikov, Dmitrii; Goncharov, Igor; Donkov, Nikolai (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2014)
Femoral neck fractures are a common insufficiency fracture in the elderly. The application of ceramic coatings on metallic materials represents an effective way to formation of advanced surfaces of unipolar and bipolar modular prosthesis for joint arthroplasty. The enhancement of mechanical properties such as hardness parameters up to 14 GPa, adhesion strength up to 50 N and low friction coefficient of multilayer coatings, with strong tendency to decrease in fluids (0.07), effective Young’s modulus, toughness, elastic recovery and wear resistance of the coatings is very important for tribological performance of the next generation of ceramic coated modular prosthesis. The joint femoral head surfaces with nano structural multilayer coatings demonstrate improved biocompatibility due to wettability increasing and fluid friction characteristics advancing.